Penerapan Kombinasi Model Discovery Learning dengan Problem-Based Learning dalam Pembelajaran Abad 21: Systematic Literature Review - Krisna Yana, Putu Sastra; Agustini, Ketut; Suartama, I Kadek (Jayapangus Press, 2025)
21st century education demands a profound transformation in the learning approach, from previously being centered on teachers and content mastery alone, to emphasizing more on developing 21st century skills, such as critical thinking, problem solving, creativity, communication, and collaboration. A relevant approach to answer this challenge is the combination of the Discovery Learning model with Problem-Based Learning. This study aims to evaluate the application of the combination of the Discovery Learning model with Problem-Based Learning in developing 21st century skills at various levels of formal education. The study was conducted using the Systematic Literature Review (SLR) method with PRISMA guidance, this study analyzed 18 selected articles from the 2021-2024 period identified through Google Scholar, the Garuda Portal and Mendeley. Research on the combination of the Discovery Learning model with Problem-Based Learning was found the most in 2024 at various levels and various subjects/courses and had an impact on various variables. The results of the study show a positive effect of the combination of the Discovery Learning model with Problem-Based Learning on critical thinking skills and problem-solving skills from elementary school to college in science and mathematics subjects. In conclusion, the application of a combination of Discovery Learning and Problem-Based Learning models is an empirically proven approach to strengthening students' core competencies in facing the challenges of the 21st century.